2012
DOI: 10.1016/j.ridd.2011.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating children with Attention-Deficit/Hyperactivity Disorder, Conduct Disorder, Learning Disabilities and Autistic Spectrum Disorders by means of their motor behavior characteristics

Abstract: The study was designed to investigate the discriminant validity of the Motor Behavior Checklist (MBC) for distinguishing four group of children independently classified with Attention-Deficit/Hyperactivity Disorder, (ADHD; N=22), Conduct Disorder (CD; N=17), Learning Disabilities (LD; N=24) and Autistic Spectrum Disorders (ASD; N=20). Physical education teachers used the MBC for children to rate their pupils based on their motor related behaviors. A multivariate analysis revealed significant differences among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 49 publications
1
16
0
2
Order By: Relevance
“…MBC for children. In this study, we introduce the MBC for children (Efstratopoulou, Janssen, & Simons, 2012) as a screening instrument to measure the motor-related behavioral symptoms of elementary school-aged children. The MBC for children is a Behavior Scale designed to be completed by the physical educator teacher who knows the child well enough to rate his or her motor behavior.…”
Section: Assessment Instrumentsmentioning
confidence: 99%
“…MBC for children. In this study, we introduce the MBC for children (Efstratopoulou, Janssen, & Simons, 2012) as a screening instrument to measure the motor-related behavioral symptoms of elementary school-aged children. The MBC for children is a Behavior Scale designed to be completed by the physical educator teacher who knows the child well enough to rate his or her motor behavior.…”
Section: Assessment Instrumentsmentioning
confidence: 99%
“…These results indicate that the MBC is a useful tool to discriminate between the core symptoms of ADHD, conduct disorder, and ASD. 9 In another study, Efstratopoulou et al 10 Although no consensus can be found in the literature on the steps for a cross-cultural adaptation process, scholars agree that this process must go beyond a simple translation, 11,12 since a translation alone does not guarantee the reliability and construct validity of the instrument. 11 Several steps are necessary to ensure a careful process of cross-cultural adaptation of an instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst studies without comparison controls groups have obvious limitations, we include them for the sake of the descriptive data they provide. Consequently, we exclude a) studies not written in English; b) animal studies; c) single case studies; d) studies which do not report behavioural findings (for example, Dawson, Warrenburg, and Fuller (1983), which focuses on lateralization of brain activity but not performance); e) studies focussing on interventions; f) studies focussing on motor stereotypies as consistent with repetitive and restricted behaviours and interests, and g) studies which, by 'abnormal motor behaviour', actually investigate physical, so-called 'problem' behaviours (externalizing, 'acting out', rule breaking: e.g., Efstratopoulou, Janssen, & Simons, 2012). In terms of sample, we exclude studies whose sample focuses on a) children or adults described as having 'mental retardation' or being 'subnormal' or 'psychotic' (prior to 1975), who cannot therefore be confidently identified as autistic; b) children or adults described merely as having 'learning disabilities' or as being 'savants', for the same reason; c) siblings of autistic individuals (a group we discuss further below); and d) children or adults with another developmental disorder, such as attentiondeficit/hyperactivity disorder (ADHD) or Fragile X syndrome, with comorbid autism or autistic traits.…”
mentioning
confidence: 99%